In situ 3D observations of capillary-driven flows in parallel arrangements of rigid fibres using X-ray microtomography. (June 2022) - Balbinot, C.; Martoïa, F.; Dumont, P.J.J.; Orgéas, L.; Bloch, J.-F.; Rolland du Roscoat, S.; Boller, E.; Flin, F.; Carion, P.; Latil, P.
Graphical abstract: Abstract: Capillary-driven impregnation phenomena occurring in fibre bundles during the processing of composite materials are complex and still not fully understood. Hence, synchrotron X-ray microtomography was used to characterise the longitudinal propagation of the flow front within a parallel arrangement of rigid fibres. The analysis of 3D images enabled the fluid-air interface curvatures, triple line lengths, and local contact angles to be quantified during wetting and dewetting experiments. The results showed that even in quasi-static situations, local contact angles exhibited significant variations along the fibres. These variations also depended on the wetting/dewetting state. The transverse capillary forces measured at the fibre scale from the analysis of 3D images were shown to be of the same order of magnitude as the longitudinal capillary forces. Local curvatures of the fluid-air interface and the resulting estimate of the average capillary pressure proved the relevance of a mesoscale capillary pressure model adapted for fibre bundles.